Students’ Perception toward the Implementation of Peer-Assessment in Writing; Before and After Revision - Husni Mubarok (Soegijapranata Catholic University, 2017)
This study was aimed at elaborating students’ perception toward the implementation of peer assessment in writing class either before or after revision. Writing becomes one of skills which should be mastered by students in order to get higher level of literacy. Writing is a productive skill which asks students to arrange words and organize them into good writing which could be understood by readers. The success of writing is determined by the writing process itself starting from planning, first draft writing, revising, and editing. One of the strategies used in teaching writing is by implementing peer assessment. Peer assessment strategy becomes one of important parts in the process of writing because there will be feedback or suggestion from peers in doing a review. The number of the subject of this research was students in second semester of the English Education Department of UNISNU Jepara. This research was conducted on even semester. The total number of the students, which became respondents, was 37 students of English Education Department. The research design used was qualitative research which measured students’ perceptions of the implementation of peer assessment in writing: before and after revision. The result showed that before revision, students had negative perception toward their own writing. After revision, they had positive perceptions toward peer assessment strategy. Those included usefulness and meaningfulness, nature of feedback, reality of feedback, precision, validity, fairness, and personal goal-setting. Besides that, the score after revision (7.9) was higher than the score before revision (6.62). It meant that the result showed the increasing of students’ score after revision.